Green Consumers, Greenwashing and the Misperception of Environmental Quality - Luca Lambertini; Giuseppe Pignataro; Alessandro Tampieri (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2014)
In this paper we analyse a setup where consumers are heterogeneous in the perception of environmental quality. The equilibrium is verified in a setting with horizontal and vertical (green) differentiation. Profits are increasing in the misperception of quality, while, the investment in green quality decreases the more the goods are substitutes. We further consider the introduction of either an emission tax or an environmental standard. The former rises the investment in environmental quality due to the higher cost of production, whereas in equilibrium quality always improves after the introduction of the latter. We show that an optimal environmental standard is an effective regulatory instrument against greenwashing and that the efficacy of the interventions is conditioned to the damage distribution and the aggregate level of emission.
Keywords: L13; L51; Q50; 330